A new species of Pseudosmittia Edwards (Diptera, Chironomidae) from Hongjiannao National Nature Reserve, China - Nie, Jiaxin; Liu, Chunmian; Zhang, Yajin; Li, Xiaomin; Jia, Xingyue; Tan, Jiangli; Liu, Wenbin (Zootaxa, 2026)
Pseudosmittia hongjiannaoensis Liu, sp. nov. is described and illustrated based on adult males collected from Hongjiannao National Nature Reserve, Shaanxi, China. Morphological identification, DNA barcoding comparison, and mitochondrial genome (mitogenome) assembly were employed to characterize the new species. The mitochondrial COI barcode sequences and mitogenomic data support its distinction from previously known Pseudosmittia species. The minimum interspecific K2P distance between P. hongjiannaoensis Liu, sp. nov., and its closest congener was 15.1%, with an average distance of 23.0%, substantially exceeding the commonly referenced threshold for insect species delimitation. The new species can be distinguished by the unique shape of the inferior volsella and the lack of an anal point. An updated key to the adult males of Pseudosmittia from China is provided. This discovery of the new species enriches the known diversity of the genus in East Asian inland freshwater ecosystems and highlights the ecological significance of the Hongjiannao Lake as a unique wetland habitat.